2020
DOI: 10.4236/abcr.2020.94011
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Knowledge, Attitudes on Risk Factors and Means of Screening by Medical Students from Lomé, Togo

Abstract: Background: Breast cancer is the leading cause of cancer-related death in women around the world. The objective of this study was to assess knowledge and attitudes about breast cancer screening among students in the Faculty of Health Sciences at the University of Lomé. Methods: This was a prospective descriptive transversal study conducted among students enrolled in the Faculty of Health Sciences (FSS) of the University of Lomé (UL) in the 2019 school year account 2020. The purpose of this study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
9
2
Order By: Relevance
“…Twenty six seventy four percent of schoolgirls reported that bearing money on breasts was a common risk factor of breast cancer according to our findings. These results do not corroborate with those found by Darre T, et al, in Togo which demonstrated that the answer of students to risk factors of breast cancer has been globally satisfying and the risk factors settled for the breast cancer comprised reproductive factors and hormonal (menarche, delayed menopause, nulliparous, oestrogens exogenous), the genetic, age, adiposity, alcohol consumption and meanness [11]. On the other hand, a feeble knowledge of risk factors ends often up by bad attitudes and bad behaviors concerning the maintenance of safe lifestyle and screening methods of breast cancer [13].…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Twenty six seventy four percent of schoolgirls reported that bearing money on breasts was a common risk factor of breast cancer according to our findings. These results do not corroborate with those found by Darre T, et al, in Togo which demonstrated that the answer of students to risk factors of breast cancer has been globally satisfying and the risk factors settled for the breast cancer comprised reproductive factors and hormonal (menarche, delayed menopause, nulliparous, oestrogens exogenous), the genetic, age, adiposity, alcohol consumption and meanness [11]. On the other hand, a feeble knowledge of risk factors ends often up by bad attitudes and bad behaviors concerning the maintenance of safe lifestyle and screening methods of breast cancer [13].…”
Section: Discussioncontrasting
confidence: 78%
“…In our series 61.75% of schoolgirls are aware of the existence of breast cancer. On the other hand in the study of Darre T, et al, in Togo, female medical students in general were aware of the existence of breast cancer [11]. This low knowledge rate on breast cancer could be justified by lack of sensitization on the condition in different areas throughout the country.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations